Language Politeness in the Digital Era: Analysis of TikTok Comments on Fuji's Posts - Daulay, Sholihatul Hamidah; Handriani, Puput; Dinata, Annisa Putri (Kajian Linguistik dan Sastra, 2026)
This research focuses on analyzing the politeness strategies employed by internet users in their comments on celebrity Fuji’s TikTok posts. The freedom of expression on social media fosters a variety of verbal interactions, ranging from courteous to discourteous. Utilizing a qualitative approach with pragmatic discourse analysis based on Brown and Levinson’s politeness theory, data were collected from ten screenshots of TikTok comments and analyzed in depth. The findings reveal that users implement several politeness strategies: positive politeness, negative politeness, off record, and bald on record. The bald on record strategy predominates, indicating a tendency among social media users to express opinions directly and sometimes harshly. This trend signifies a shift in traditional norms of politeness within digital communication. The study highlights the necessity of digital literacy to maintain ethical language use and foster social harmony in online environments. Abstrak Penelitian ini berfokus pada analisis strategi kesantunan yang digunakan oleh pengguna internet dalam komentar mereka pada unggahan TikTok selebriti Fuji. Kebebasan berekspresi di media sosial memicu berbagai interaksi verbal, mulai dari yang santun hingga yang tidak santun. Dengan menggunakan pendekatan kualitatif dengan analisis wacana pragmatik berdasarkan teori kesantunan Brown dan Levinson, data dikumpulkan dari sepuluh tangkapan layar komentar TikTok dan dianalisis secara mendalam. Temuan menunjukkan bahwa pengguna menerapkan beberapa strategi kesantunan: kesantunan positif, kesantunan negatif, off record (tidak langsung), dan bald on record (tanpa basa-basi). Strategi bald on record mendominasi, yang menunjukkan kecenderungan pengguna media sosial untuk mengekspresikan pendapat secara langsung dan terkadang kasar. Tren ini menandakan adanya pergeseran norma kesantunan tradisional dalam komunikasi digital. Studi ini menekankan pentingnya literasi digital untuk menjaga penggunaan bahasa yang etis dan memupuk harmoni sosial di lingkungan daring.